'Notorious Beyond Any Other European Woman of Her Generation': The Case of Count(ess) Sarolta/Sándor Vay. (2nd January 2018) - Török, Zsuzsa
ABSTRACT: The paper investigates the curious case of the Hungarian Count(ess) Sarolta/Sándor Vay, journalist and writer, but, above all, a notorious gender bender in late nineteenth-century Austro-Hungarian Monarchy. The article examines her case in the context of the history of European cross-dressing and of narrative transvestism. The author argues that nineteenth-century dandyism provided an effective cultural framework for Vay's contemporaries to accept her unconventional presence in fin-de-siècle Hungarian society. Moreover, she claims that Vay's narrative transvestism may also be construed within the cultural phenomenon of dandyism, as her writing practices prove to be further instruments for her self-fashioning. Finally, she concludes that Vay's gender performance and narrative transvestism become illustrative examples of instances that both frame and confuse accepted cultural patterns, destabilize gender binarism, and participate in its maintenance.